Wear Behavior of AlSi10Mg Alloy Produced by Laser‐Based Powder Bed Fusion and Gravity Casting. Issue 10 (25th August 2021) - Tonolini, Pietro; Montesano, Lorenzo; Tocci, Marialaura; Pola, Annalisa; Gelfi, Marcello
Abstract : Herein, the sliding wear behavior of AlSi10Mg samples realized using laser‐based powder bed fusion (LPBF) is investigated via pin‐on‐disc (PoD) tests, before and after T6 heat treatment. The changes in the microstructure, density, and hardness induced by heat treatment are correlated with the tribological behavior of the alloy. Furthermore, short wear tests are conducted and the resulting wear tracks are investigated through scanning electron microscopy (SEM), equipped with an energy‐dispersive spectroscopy (EDS) microprobe to elucidate how the wear mechanisms evolve with sliding distance. For comparison, gravity cast (GC) AlSi10Mg samples are also characterized and tested. The as‐built additive manufacturing (AM) sample exhibits the lowest wear rate and coefficient of friction because of its high hardness and relative density, whereas the heat‐treated sample shows the worst behavior in comparison with the GC samples. The results suggest a significant influence of porosity on the wear behavior of AM alloys. Abstract : The wear behavior of AlSi10Mg alloy manufactured by additive manufacturing (AM) and by gravity casting (GC) methods is investigated in the as‐produced condition and after T6 heat treatment. As‐built AM samples exhibit the highest wear resistance, whereas after T6 they show a worsen behavior than the GC samples. Porosity enlargement after T6 and the Si morphology can explain these findings.